Transposon-derived transcription factors across metazoans - Mukherjee, Krishanu; Moroz, Leonid L. (Frontiers in Cell and Developmental Biology, 2023)
Transposable elements (TE) could serve as sources of new transcription factors (TFs) in plants and some other model species, but such evidence is lacking for most animal lineages. Here, we discovered multiple independent co-options of TEs to generate 788 TFs across Metazoa, including all early-branching animal lineages. Six of ten superfamilies of DNA transposon-derived conserved TF families (ZBED, CENPB, FHY3, HTH-Psq, THAP, and FLYWCH) were identified across nine phyla encompassing the entire metazoan phylogeny. The most extensive convergent domestication of potentially TE-derived TFs occurred in the hydroid polyps, polychaete worms, cephalopods, oysters, and sea slugs. Phylogenetic reconstructions showed species-specific clustering and lineage-specific expansion; none of the identified TE-derived TFs revealed homologs in their closest neighbors. Together, our study established a framework for categorizing TE-derived TFs and informing the origins of novel genes across phyla.